The literature review of Ollier disease - Wejjakul, Witchuree; Pruksakorn, Dumnoensun; Sirirungruangsarn, Yuddhasert; Luevitoonvechkij, Sirichai; Khunsree, Songsak; Vaseenon, Tanawat (Biomedical Sciences and Clinical Medicine, 2023)
Ollier disease is a rare disease with an incidence 1:100,000. It is a multiple benign hyaline-cartilaginous-forming tumor at metaphysis or extended to diaphysis of bone. This paper reviews the Ollier disease and its general, pathogenesis, clinical presentations, investigation findings and the treatment which still has no consensus.